Addition of rituximab to fludarabine and cyclophosphamide in patients with chronic lymphocytic leukaemia: a randomised, open-label, phase 3 trial - Hallek, Michael; Hensel, Manfred (The lancet, 2010)
Background - On the basis of promising results that were reported in several phase 2 trials, we investigated whether the addition of the monoclonal antibody rituximab to first-line chemotherapy with fludarabine and cyclophosphamide would improve the outcome of patients with chronic lymphocytic leukaemia. - Methods - Treatment-naive, physically fit patients (aged 30-81 years) with CD20-positive chronic lymphocytic leukaemia were randomly assigned in a one-to-one ratio to receive six courses of intravenous fludarabine (25 mg/m2 per day) and cyclophosphamide (250 mg/m2 per day) for the first 3 days of each 28-day treatment course with or without rituximab (375 mg/m2 on day 0 of first course, and 500 mg/m2 on day 1 of second to sixth courses) in 190 centres in 11 countries. Investigators and patients were not masked to the computer-generated treatment assignment. The primary endpoint was progression-free survival (PFS). Analysis was by intention to treat. This study is registered with ClinicalTrials.gov, number NCT00281918. - Findings - 408 patients were assigned to fludarabine, cyclophosphamide, and rituximab (chemoimmunotherapy group) and 409 to fludarabine and cyclophosphamide (chemotherapy group); all patients were analysed. At 3 years after randomisation, 65% of patients in the chemoimmunotherapy group were free of progression compared with 45% in the chemotherapy group (hazard ratio 0·56 [95% CI 0·46-0·69], p<0·0001); 87% were alive versus 83%, respectively (0·67 [0·48-0·92]; p=0·01). Chemoimmunotherapy was more frequently associated with grade 3 and 4 neutropenia (136 [34%] of 404 vs 83 [21%] of 396; p<0·0001) and leucocytopenia (97 [24%] vs 48 [12%]; p<0·0001). Other side-effects, including severe infections, were not increased. There were eight (2%) treatment-related deaths in the chemoimmunotherapy group compared with ten (3%) in the chemotherapy group. - Interpretation - Chemoimmunotherapy with fludarabine, cyclophosphamide, and rituximab improves progression-free survival and overall survival in patients with chronic lymphocytic leukaemia. Moreover, the results suggest that the choice of a specific first-line treatment changes the natural course of chronic lymphocytic leukaemia. - Funding - F Hoffmann-La Roche.
Available online 30 September 2010
Gesehen am 03.03.2023